Caveats to the use of MTT, neutral red, Hoechst and Resazurin to measure silver nanoparticle cytotoxicity. (5th January 2020) - Mello, Danielle F.; Trevisan, Rafael; Rivera, Nelson; Geitner, Nicholas K.; Di Giulio, Richard T.; Wiesner, Mark R.; Hsu-Kim, Heileen; Meyer, Joel N.
Abstract: The extensive use of silver nanoparticles (AgNPs) in manufactured products will inevitably increase environmental exposure, highlighting the importance of accurate toxicity assessments. A frequent strategy to estimate AgNP cytotoxicity is to use absorbance or fluorescent-based assays. In this study we report that AgNPs – with or without surface functionalizations (polyvinyl pyrrolidone or gum arabic), and of different sizes (2–15 nm) – can interfere with the spectrometric quantification of different dyes commonly used in cytotoxicity assays, such as 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT), neutral red (NR), Hoechst, and Resazurin. Some AgNP types caused more interference than others, which was dependent on the assay. Overall most AgNPs caused the direct reduction of MTT, as well as Hoechst and NR fluorescence quenching, and absorbed light at the same wavelength as NR. None of the AgNPs tested caused the direct reduction of Resazurin; however, depending on AgNP characteristics and concentration, they may still promote fluorescence quenching of this dye. Our results show that AgNPs with different size and coatings can interfere with spectroscopy-based assays to different degrees, suggesting that their cytotoxicity may be underestimated or overestimated. We suggest that when using any spectroscopy-based assay it is essential that each individual nanoparticle formulation be tested first for potential interferences at all intended concentrations. Graphical abstract: Image 1 Highlights: Most of the AgNPs tested and silver ions caused the direct reduction of MTT. Some AgNPs caused fluorescence quenching of Hoechst and Neutral red dyes. All AgNPs tested showed negligible interference with Resazurin dye. Interference is dependent on the AgNP type and dye. We recommend interference testing of AgNP with spectroscopy-based assays.